Efficient Algorithms for Hierarchical Graph-Based Segmentation Relying on the Felzenszwalb–Huttenlocher Dissimilarity - Cahuina, Edward Cayllahua (2018)
The research leading to these results has received funding from the French Agence Nationale de la Recherche, grant agreement ANR-15-CE40-0006 (CoMeDiC), the Brazilian Federal Agency of Support and Evaluation of Postgraduate Education (program CAPES/PVE: grant 064965/2014-01), the Peruvian agency Consejo Na-cional de Ciencia, Tecnolog´ıa e Innovaci´on Tecnol´ogica CONCYTEC (contract N-101-2016-. FONDECYT-DE). The first author would like to thank Brazilian agencies CNPq and CAPES and Peruvian agency CONCYTEC for the financial support during his thesis.